Pedagogical training of higher education teachers and their implications in the teaching mode - Correia, Hermenegilda (2018)
The present study seeks to address the pedagogical training of higher education teachers and the implications for the ways of teaching. The study was conducted at a faculty of a Mozambican university, hereinafter referred to by the pseudonym João Luís Cabral University. Thus, our research seeks to understand how the pedagogical training practices of higher education teachers are characterized and what implications are recognized and can be observed in the way they teach. In order to answer our starting question, we chose to conduct our research by means of a case study, since the phenomenon occurs in a context of its own specificity. We also chose to approach the study in light of the interpretative paradigm. This option is due to the fact that it fits in with our concern of seeking to understand the pedagogical training practices of teachers. Given the nature of our study, we selected the following data collection techniques, namely: semi-structured interviews, focus group and classroom observation. Next, in order to answer our questions, we selected not only a number of subjects directly involved in pedagogical training, but also some direct beneficiaries of this training, ie students, teachers, trainers and the director of the University. Pedagogical training was perceived by our interviewees as an essential and indispensable tool to be able to properly guide the teaching-learning process, although their practices express a contrary tendency, as there was a poor application of the feedback method and an excessive predominance of the expository method, making evident the use of a transmissive didactic model more focused on the fulfillment of the teaching program than on learning.